Oliver Wendell Holmes Jr., pragmatism, and the jurisprudence of Agon : aesthetic dissent and the common law - Mendenhall, Allen, 1983- (Bucknell University Press, 2017)
Oliver Wendell Holmes Jr.'s dissents are influential because of their literary qualities of superfluity and energy he inherited from Emerson. The aesthetic style of his dissents reflects his theory of the common law that rejected depictions of fixed and unchanging rules in favor of an evolutionary view.